Managing Supply Chain - Subha, M.V. (Indian Journal of Marketing, 2004)
Fast delivery is critical in most markets today. Many companies try to meet their market demand by carrying higher inventories. Inventory is a hedge against lead-time. Higher levels of inventory are often maintained because the company is unable to produce the material within the time demanded by the market. Analyzing the processes in supply chain can identify the causes and facilitate solutions to reduce overall throughput time. Compressing time, the chain of events from the time a customer places an order until the order is satisfied can provide a competitive edge without the burden of carrying excessive inventory. A supply chain is the process of moving goods from customer order through the raw materials stage, supply, production, and distribution of products to the customer. Supply chain in organizations vary depending upon the size of the organization and the type of product manufacturing. These networks obtain supplies and components, change these materials into finished products and then distribute them to the customer. Managing the chain of events in this process is what is known as supply chain management. Effective management must take into account coordinating all the different pieces of this chain as quickly as possible without losing any of the quality or customer satisfaction, while trying to keep costs down.